Evaluation of the Performance of on Street Parking on AL-Jumhoryia Street in Baghdad City - Ahmed, lamia Abduljaleel (Basrah Journal for Engineering Sciences, 2007)
This paper describes a study of traffic behavior at AL-Jumhoryia street in Baghdad city. The objective is to use simulation program OSPSM to evaluate the performance of on street parking. The first stage of this research project takes the basic measurements carried out using video camera. The basic measurements are traffic flow, operating speed, parking time, unparking time, gap, and average duration. The second stage of the simulation program OSPSM was to run it using all the observed input parameters to obtain some measures of effectiveness such as the delays caused to through vehicles, the delays caused to parked vehicles, reduction in capacity, turnover rate, Parking Index, Parking accumulation. The main conclusion to the performance of on street parking is that it is reasonable, the average delay of parked vehicles and through vehicles at AL-Jmahory street is accepted value.